(untitled) (MMIT Proceedings, 2024)
This article is devoted to the problem of solving the issue of parents’ preference for a preschool institution. The reasons for the behavior of consumers (parents) when choosing a kindergarten for a child, the degree of awareness about the preschool institution, sources and channels of information, as well as the most important indicators of the preschool institution’s activity that determine their choice are analyzed.